To Study the Stress-Strain Hysteresis in Timber at Rooms Temperature and Different R.H. - Sanyal, S. N.; Millen, R. C. (Indian Forester, 1980)
In wood the influence of hygroscopic moisture is very important. Small elastic deformation imposed for a period of time may turn into plastic deformation. Hooke’s Law is not very much applicable in a wide range for a complicated material like wood. Stress strain behaviour is therefore differen in wood as compared to other elastic bodies. In this paper the authors have studied, at room temperature and different R.H. the stress strain hysteresis phenomenon of Chir species. The hysteresis area reflects the work done for cycle which is lost as heat and other form of energy and is a measure of the non reversable process of stress strain in the case of wood.